(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India is a country with principles based on traditional ideologies and moral concepts, but they are rarely incorporated into modern living styles. Getting physical with the opposite sex, fun friendship, dating, emotional exploitations, mutual exploitation, lust, sex before marriage, sex with other men or women does not form a structure of Indian culture or tradition. But Bhagat’s characters exhibit such emotional packages as a part of their modern living to encourage cultural degradation and modern cultural revolution. Chetan Bhagat has focused the limelight in the modern culture and travels by highlighting his life and the existence of other people whom he has encountered and understood through his literary works. Bhagat in One Indian Girl reveals the life and attitude of an Indian girl, Radhika, who is extremely intelligent, her annual compensation is equal to forty-eight lakh rupees a year. Her dating experience begins in New York where her beauty was appreciated and accepted. This paper explores the changes in the modern Indian culture that was inculcated in the society by the invaded dating culture.